Enhancing Material Tracking Practices of Material Management in Construction Project - Kasim, Narimah Binti; Kusumaningtias, Rohmawati Binti; Sarpin, Norliana Binti (International Journal of Sustainable Construction Engineering and Technology, 2020)
Construction materials and equipment on a single project can constitute for up to 70% of the total project cost. It makes the managing of construction materials an important aspect and needed to be highlighted at every phase in construction project. Material tracking practice in material management can helps to provide timely information of the materials availability at the construction site and the storage yard. However, material tracking practice in material management in construction industry have been using manual method and has many drawbacks. Thus in this research, current practices of material tracking were studied, problems of material tracking practices in material management were identified and the key factors for enhancing material tracking in material management for Malaysian construction project were suggested. The study was conducted with 54 individuals that involved from G7 class of contractors within 3 main states which are Johor Bahru, Selangor and Wilayah Persekutuan (Kuala Lumpur and Putrajaya). This research is statistically descriptive orientation and questionnaire is being used as research instrument with respondent rate of 54%. Data collected was analysed using the Statistical Package for the Social Science (SPSS) 24.0 software. The method of analysis that being used in this research are percentage, frequency and mean score value. The results from this study shows that the current practices of material tracking were to track and record the delivery schedule of materials in computerised system. Other than that, the practices used were manual tracking, identification, calculation and documentation of the construction material. The drawbacks of the current practices such as lack of materials tracking in terms of timely ordering, problems in manual material tracking on site and at storage yard, and issues in tracking of the material by construction workers. That is the motivations on why material tracking practices are as important and need to be enhanced as it never been due to the availability and opportunity provided by current technologies to improve the efficiency and to minimize or possibly eliminate the unnecessary problems.